Classifications of Solutions of Second Order Nonlinear Neutral Delay Difference Equations With Positive and Negative Coefficients - Thandapani, E.; Vijaya, M. (Sarajevo Journal of Mathematics, 2024)
In this paper the authors classified all solutions of the following equation $$ Δ\Big( a_{n}\Big( Δ (x_{n}+c_{n}x_{n-k})\Big) ^{α}\Big )+p_{n}f(x_{n-l})-q_{n}g(x_{n-m}) = 0$$ into four classes and obtain conditions for the existence/nonexistence of solutions in these classes. Examples are provided to illustrate the results. 2000 Mathematics Subject Classification. 39A11